Obtenção e performance de biocatalisadores: imobilização e efeito de aditivos químicos - Torres, Juliana Arriel (2017)
Peroxidases are enzymes with various applications, mainly in the degradation of organic compounds. Researches have been developed with these enzymes obtained from various vegetable sources, mainly agroindustrial waste. However, these biocatalysts are subject to inhibition, as for example by the final products of phenolic pollutants degradation. To overcome this limitation, chemical additives can be incorporated into the reaction medium, besides immobilizing these enzymes in different supports. In this work, were applied peroxidases obtained from turnip and soybeans, an agroindustrial residue, in the degradation of standard phenolic compounds in the presence of the additives polyethylene glycol (PEG) and triton X-100. It was evaluated also the degradation of total phenolic compounds from coffee processing wastewater (CPW) using soybean peroxidase (SP). In addition, another alternative was sought to improve the enzymatic stability, as well as to facilitate the removal of the biocatalyst and to enable the reuse of this, immobilizing this biocatalyst in activated carbon (AC), which was synthesized using the solid residue collected from the SP extraction. The immobilization of SP in AC (SP-AC) was evaluated at different time conditions, enzyme loading, pH and temperature. An activated carbon/magnetite composite was synthesized to facilitate the removal of the immobilized biocatalyst with the application of a magnetic field. Characterization techniques were performed in different materials. The turnip and soybean peroxidases were efficient in the degradation of the phenolic compounds, however, only for phenol and caffeic acid (pH 3.0), the protective effect of the additives was observed. PS presented 31.15% of CPW oxidation, however, in the presence of PEG and triton X-100 no influence on the oxidation of phenolic compounds was observed. The AC presented a high specific surface area of 1,603 m2 g-1, which makes it ideal for immobilization of enzymes, besides having been obtained with full use of biomass, with minimal waste generation. SP-AC immobilization reached 100% in the support:enzyme of 1.0:0.05 (m/m), pH 3.0, temperature 40 ° C for a period of 1 hour. SP-AC was reused for 10 cycles, presenting a decline in the first cycle and remaining constant until the last cycle. This drop may be associated with inhibition of the enzyme by the reaction products, once the enzyme has not been leached. Despite the advantage of using AC as a support for enzyme immobilization, its recovery from the reaction medium is a tedious process. To overcome this inconvenient a magnetic composite was synthesized. The immobilization of the magnetic SP-AC was 100% in the support:enzyme relationship of 1.0:0.05 (m/m), pH 3.0, temperature 50 ° C for a period of 7 hours. This magnetized immobilized biocatalyst was reused for 11 cycles, with a decrease of approximately 30% over the first cycle and remaining constant until the last. It is concluded that using additives in the oxidation of phenolic compounds of the CPW does not bring benefits, which represents a positive response from the economic point of view. The AC obtained represents a promising support for SP immobilization, with maximum biomass utilization, and the synthesized magnetic composite facilitates the recovery and reuse of the immobilized SP.